Specific heat and angle-resolved photoemission spectroscopy study of the superconducting gaps in LiFeAs - Stockert, Ulrike; Abdel-Hafiez, M.; Evtushinsky, D. V.; Zabolotnyy, V. B.; Wolter, A. U. B.; Wurmehl, S.; Morozov, I.; Klingeler, Rüdiger; Borisenko, S. V.; Büchner, B. (Physical review. B, Condensed matter and materials physics, 2011)
We present specific-heat, cp, and angle-resolved photoemission spectroscopy (ARPES) data on single crystals of the stoichiometric superconductor LiFeAs. A pronounced anomaly is found in cp at the superconducting transition. The electronic contribution can be described by two s-type energy gaps with magnitudes of approximately Δ1=1.2 meV and Δ2=2.6 meV and a normal-state γ coefficient of 10 mJ/mol K2. All these values are in agreement with ARPES results.